2016
DOI: 10.5539/ies.v9n10p47
|View full text |Cite
|
Sign up to set email alerts
|

Employment of Active Learning at HEIs in Bangladesh to Improve Education Quality

Abstract: In recent years, education quality and quality assessment have received a great deal of attention at Higher Education Institutions (HEIs) in Bangladesh. Most of the HEIs in Bangladesh face severe resource constraints and find it difficult to improve education quality by improving inputs, such as better infrastructure and modernized classroom facilities. Thus, in response to the present government's demand to improve the quality of education at HEIs in Bangladesh, it is imperative to formulate plans that are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…, 2017; Islam et al. , 2017; Islam and Shafiq, 2016; Chowdhury, 2016; Monem and Baniamin, 2010). However, research work on considering students' voices to identify student preferred learning needs and/or requirements and improving or evaluating teaching techniques of management education, particularly in the affiliated government colleges are yet to find difficult (Rabbani and Chowdhury, 2014).…”
Section: Management Education In National Universitymentioning
confidence: 99%
“…, 2017; Islam et al. , 2017; Islam and Shafiq, 2016; Chowdhury, 2016; Monem and Baniamin, 2010). However, research work on considering students' voices to identify student preferred learning needs and/or requirements and improving or evaluating teaching techniques of management education, particularly in the affiliated government colleges are yet to find difficult (Rabbani and Chowdhury, 2014).…”
Section: Management Education In National Universitymentioning
confidence: 99%
“…Necessary infrastructural support, internet facility, positive motivation, pre and in-service training, professional learning community, eliminating the pressure on the teacher etcetera can be helpful for enhancing pedagogical skill through CPD (Faruki, Haque, & Islam, 2019;Alam, Mishra, & Shahjamal, 2014;Islam, 2008;and, Khan, 2008). But the teachers' CPD in Bangladesh should be cost-effective as the government of the country is still in a financial constraint (Chowdhury, 2016). In this situation, smartphone based CPD programmes can be applicable for Bangladeshi College teachers (Pouezevara, 2016).…”
Section: Suggestions For Enhancing Pedagogical Skills Through Continuing Professional Development Practicesmentioning
confidence: 99%
“…Active learning is preferentially used by subject specialist lecturers with educational specialties (Addy et al 2015) which shows that training of lecturers does play a role in the effective use of Active learning strategies. Studies have also shown how lecturers or teachers perceived and acted upon government policy with regards to reforming current traditional classroom teaching practice to that which include Active learning strategies in both Ethiopia, Bangladesh, Qatar and China (Casale 2010;Chowdhury 2016;Qureshi et al 2016;Riley 2013 ).…”
Section: Perceptions Of Lecturers Of Active Learning In Higher Educationmentioning
confidence: 99%